Structure and Function of SLC4 Family HCO3- Transporters - Liu, Ying; Yang, Jichun; Chen, Li-Ming (Frontiers in Physiology, 2015)
The SLC4 family contains 10 members, nine of which are HCO3– transporters, including three Na+-independent Cl−/HCO3– exchangers AE1, AE2, and AE3, five Na+-coupled HCO3– transporters NBCe1, NBCe2, NBCn1, NBCn2, and NDCBE, as well as “AE4” whose Na+-dependence remains controversial. The SLC4 HCO3– transporters play critical roles in pH regulation and transepithelial movement of electrolytes with a broad range of physiological relevances. Dysfunctions of these transporters are associated with a series of human diseases. During the past decades, tremendous amount of efforts have been undertaken to investigate the topological organization of the SLC4 transporters in the plasma membrane. Based upon the proposed topology models, mutational and functional studies have identified important structural elements likely involved in the ion translocation by the SLC4 transporters. In the present article, we will review the advances during the past decades in understanding the structure and function of the SLC4 transporters.